Eu tomo medicamentos para estudar: compreendendo a experiência com Metilfenidato entre estudantes universitários - Julia de Paula Penna Palhares (2015)
Methylphenidate is a medication used in the treatment of Attention Deficit Hyperactivity Disorder (ADHD) and narcolepsy. Its consumption in Brazil and in the world is growing each year, as well as its non-medical usage for neuroenhancement, which is drawing the attention of researchers and society in general. Understanding university students medication experience with methylphenidate and the meaning they give to it, may contribute to raise knowledge about this medication and sensitize health and education professionals about the questions surrounding its use. Photovoice was the methodology chosen to access the medication experience with methylphenidate. In this approach, photographs captured by participants were used as the starting point for reflection and discussion. The interviews recordings and transcriptions constituted the data and were analyzed through Paulo Freires dialogic action theory. NVivo 10 software was used in the analysis. Data analysis resulted in three themes and six subthemes. The first theme was Entering College: Study You are not as good as you think, and the subthemes were I cant and The search for help. The second theme was The Entrance of the Medication in Life: The Medication Experience with Methylphenidate. Its subthemes were Life is beautiful, happiness is chemical: the expectations; If it is black labeled, its supposed to be stronger: the fears; The bodily effects and The control over the pharmacological treatment. The third theme was The Different Perceptions about ADHD and Neuroenhancement, in which the ambiguous and conflicting feelings of participants regarding that medication were discussed. Methylphenidate usage is surrounded with controversy and more research must be conducted to increase knowledge and debate about the theme. It is also important to discuss the methodology used at schools and university nowadays and the role of the multiprofessional team in the patients follow-up.